Tanggung Jawab Pejabat Pembuat Akta Tanah (PPAT) atas Perbuatan Melawan Hukum Menerbitkan Akta Jual Beli tanpa Sepengetahuan Penghadap (Penjual) Studi Putusan Nomor 3507K/Pdt/2023 - Rivo Tri Anggraini; Sutiarnoto; Mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
A Sale and Purchase Deed (AJB) executed by Land Deed Making Official (PPAT) can be declared invalid and canceled through court proceedings if proven defective from external, formal, and material aspects. This normative juridical research analyzes the legal strength of AJB made unlawfully by PPAT, specifically regarding PPAT's responsibility for issuing deeds without the seller's knowledge. Based on Decision Number 3507K/Pdt/2023, AJB made unlawfully loses its strength as an authentic deed and creates juridical consequences in the form of civil, administrative, and criminal liability for PPAT proven to have committed procedural and substantial violations in deed preparation.